Are compression garments effective for the recovery of exercise-induced muscle damage? A systematic review with meta-analysis - Marqués-Jiménez, D.; Calleja-Gonzalez, J.; Arratibel, I.; Delextrat, A.; Terrados, N. (Physiology & Behavior, 2016)
Purpose: The aim was to identify benefits of compression garments used for recovery of exercised-induced muscle damage.